تأثير الصورة الذهنية للعلامة التجارية على اتجاهات المستهلك وفقاً للبعد (المعرفي والسلوكي) "دراسة مسحية على العلامات التجارية للملابس الرياضية في محافظة اللاذقية" - قاسم سامر; الرحية زينة (Latakia University Journal - Economic and Legal Sciences Series, 2018)
هدفت هذه الدراسة إلى التعرف على الصورة الذهنية للعلامة التجارية ومفهومها والتعريف بمفهوم اتجاهات المستهلكين، كما تهدف الى تحليل تأثير الصورة الذهنية للعلامة التجارية على اتجاهات المستهلكين وفقا للبعد المعرفي والسلوكي. ولتحقيق ذلك قامت الباحثة بتحديد ودراسة ابعاد الصورة الذهنية وتأثيرها على اتجاهات المستهلكين، وذلك من خلال دراسة مسحية على العلامات التجارية للملابس الرياضية في محافظة اللاذقية، وتضمن مجتمع البحث على جميع مستهلكي الملابس الرياضية في محافظة اللاذقية وتم اختيار عينة البحث استناداً إلى معادلة الخطأ المعياري للنسبة المئوية وذلك عن معامل ثقة 95% وفي حالة أن نسبة مفردات مجتمع البحث التي تتوافر فيها الخاصية محل القياس =50% وبالعودة إلى الجداول الإحصائية تبين أن حجم العينة المناسب = 384 مفردة وقامت الباحثة بتوزيع 520 استبيان تم استرداد 500 استبيان منهم 480 صالحة للدراسة. ومن أهم ماتم التوصل اليه وجود تأثير ذو دلالة إحصائية بين الصورة الذهنية للعلامة التجارية وفقاً للبعد (المعرفي- السلوكي) واتجاهات المستهلكين نحو العلامات التجارية للملابس الرياضية في محافظة اللاذقية. كما قدّمت الباحثة من خلال هذه الدراسة مجموعة من المقترحات والتوصيات التي من المتوقع أن تساعد أصحاب العلامات التجارية على تعزيز ثقة المستهلكين بعلامتهم التجارية وبناء اتجاهات إيجابية نحوها. This study aimed to identify the mental image of the brand and the concept and definition of the concept of consumer trends, and aims to analyze the impact of the mental image of the brand on the consumer trends and according to the post-cognitive and behavioral. To achieve this, the researcher to identify and study the dimensions of mental image and its impact on consumer trends, through a survey on the brands of sport clothes in Lattakia province, and ensure that the research community on all consumers of sports apparel in Lattakia province will be selected sample based on the standard error of the percentage equation that 95% confidence coefficient In the case that the percentage of search terms a society in which the property is available measurement = 50% shop and return to the statistical tables showing that the appropriate sample size = 384 single and the researcher distributed 520 questionnaires were recovered 500 questionnaires were 480 valid study. The researcher found the presence of a statistically significant effect between the mental image of the brand, according to the post (cognitive - behavioral) and consumer trends toward brands of sport clothes in Lattakia province. The researcher presented through this study, a set of proposals and recommendations that are expected to help brand owners to enhance consumer confidence and business Baalamthm build positive attitudes towards it.